2014
DOI: 10.1007/s10856-014-5188-2
|View full text |Cite
|
Sign up to set email alerts
|

A one-step treatment for chondral and osteochondral knee defects: clinical results of a biomimetic scaffold implantation at 2 years of follow-up

Abstract: The increasing interest in the role of subchondral bone with regard to articular surface disease led to the development of new bioengineered strategies. Aim of this study is to evaluate the clinical and MRI outcome after the implantation of a nanostructured biomimetic three-phasic collagen-hydroxyapatite construct for the treatment of chondral and osteochondral defects of the knee in a large cohort of patients. Seventy-nine patients (63 M, 16 W), affected by grade III-IV femoral condyle or trochlea chondral le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 43 publications
5
44
0
Order By: Relevance
“…Similar positive conclusion was confirmed by the visual analogue scale and Tegner scores at 24 months after implantation [8]. These results showed that this was a good strategy for OCD treatment but abnormal magnetic resonance imaging findings were presented [9]. Another study was carried out in 11 patients for the treatment of tibial plateau lesions.…”
Section: Commercial Osteochondral Scaffolds and Clinical Performancesupporting
confidence: 70%
“…Similar positive conclusion was confirmed by the visual analogue scale and Tegner scores at 24 months after implantation [8]. These results showed that this was a good strategy for OCD treatment but abnormal magnetic resonance imaging findings were presented [9]. Another study was carried out in 11 patients for the treatment of tibial plateau lesions.…”
Section: Commercial Osteochondral Scaffolds and Clinical Performancesupporting
confidence: 70%
“…However, the outcome is heterogeneous and rather unpredictable [911]. Understanding the etiopathological patterns leading to the alteration of the articular tissues might shed some light into the healing potential of such lesions, explaining the heterogeneous results observed in osteochondral regeneration and giving possible indications to better target and further develop treatments in the future [1113]. An accurate knowledge of cellular osteochondral tissue patterns is mandatory to improve current therapies as well as to contribute to increasing the knowledge concerning different etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…Its composition is based on a collagen type-I hydroxyapatite gradient. MaioRegen® has demonstrated throughout its clinical studies that its technique is safe and that the clinical results in the short-and medium-term follow-up are efective in a large population of patients [144][145][146][147][148], even atributed beter results than other commercial scafolds ChondroMimetic TM [149] and TruFit CB TM [11,[150][151][152]. Despite the encouraging in vitro results of a wide variety of osteochondral scafolds, most are in the early stages of development.…”
Section: The Eicacy and Safety Of Diferent Treatments Of Cartilage Inmentioning
confidence: 99%